In-vivo Wound Healing and Anti-Inflammatory Activity of the Solvent Fraction of Zehneria scabra L.F. Sond (Cucurbitaceae) Leaves - Fisseha N; Hammeso WW; Nureye D; Tesfaye T; Yimer T (Journal of Experimental Pharmacology, 2022)
Nebeyi Fisseha,1 Workineh Woldeselassie Hammeso,2 Dejen Nureye,1 Tarekegn Tesfaye,1 Tesfaye Yimer3 1Department of Pharmacy, School of Pharmacy, College of Medicine and Health Sciences, Mizan-Tepi University, Mizan-Aman, South West Region, Ethiopia; 2Department of Pharmacy, College of Medicine and Health Sciences, Dilla University, Dilla, Ethiopia; 3Department of Pharmacy, College of Health Science, Debre Tabor University, Debre Tabor, EthiopiaCorrespondence: Nebeyi Fisseha, PO Box: 260, Mizan-Aman, Ethiopia, Tel +251913214835, Email nebeyifisseha@gmail.comBackground: Wounds continue to be a difficult clinical problem, with early and late consequences causing significant morbidity and death. As a result, proper wound management is critical. In addition to contemporary medicine, medicinal herbs serve an essential role in the treatment of wounds and bacterial infections. Z. scabra is a medicinal plant that has traditionally been used to treat wounds. However, there are no scientific reports on solvent fraction wound healing activities. As a result, the current study presents a scientific assessment of the wound healing ability of the solvent fractions of Z. scabra leaves.Methods: The leaves were crushed and macerated three times in 80% methanol. Chloroform, ethyl acetate, and aqueous fractions of simple ointment at 5% w/w and 10 percent w/w strengths were prepared using the fusion technique based on the British Pharmacopoeia. Excision and incision wound models were used to assess the solvent fractions’ wound healing activities. The anti-inflammatory efficacy of crude and solvent fractions was tested in mice utilizing a carrageenan-induced hindpaw edema model.Results: In rats, a test dose of 2000 mg/kg of the 10% w/w crude extract ointment was found to be safe. Groups treated with the 5% and 10% ethyl acetate fractions of the extract experienced significant (p< 0.05 and p< 0.01) wound reduction in the excision wound model. When compared to the negative control, the length of epithelization in groups treated with 10% ethyl acetate fraction and aqueous fractions of Z. scabra was statistically significant (p 0.001). By lowering the amount of carrageenan-induced paw edema, the leaf extract and the chloroform fraction of Z. scabra demonstrated a dose-dependent anti-inflammatory effect.Conclusion: The extract showed remarkable wound healing and anti-inflammatory activity and might be recommended for the treatment of many types of human wounds.Keywords: wound healing, anti-inflammatory excision, wound model, Zehneria scabra